A grassroots development in the light of the development theories, a case study in rural India: food for life Vrindavan - Varga, László (Human Geography Journal, 2018)
In this study, the activities of a volunteer based grassroots development in rural India - Food for Life Vrindavan (FFLV) - are presented. A thorough examination of how it complies with the dimensions established in the scientific literature about grassroots and social innovations and what the characteristics of its activities are in the light of the latest trends in human development is performed. The article is organised into six sections: after a short introduction about the subject, the objectives and the layout of the paper, section 2 presents the timeline of the development industry with a particular emphasis on the process of turning from national economy boosting initiatives to the dimensions of human development. In section 3 the key elements in the literatures on the capability approach and grassroots/social innovations are presented. Section 4 introduces the case of FFLV, followed by a detailed analysis in section 5 where FFLV’s position with regards to the different perspectives is discussed. In section 6, the quantitative analysis is conducted. Concluding the paper in the final section, some reflections on the usefulness of the study are mentioned. Based on the results of the conducted research the following conclusions have been made: 1) In the beginning, Food for Life Vrindavan was an entirely volunteer based grassroots innovation. With a gradual increase in the number of people it served and subsequent expansion in it’s fields of services, it has become a social innovation. 2) The characteristics of FFLV’s activities fit into the dimensions of human development established by the United Nations based on Amartya Sen’s concept of capability approach. 3) The financial resources of FFLV are modest in comparison to the OECD financed development industry, with the former having access to merely a quarter of the latter’s “per capita” funds available for the area of activity around Vrindavan.